PREVALENCE OF ARTERIAL HYPERTENSION AND DIABETES MELLITUS AMONG CATARACT PATIENTS - V. Haykin; Y. Zdravkov; A. Isaev; S. Kostova; Iv. Tane (Trakia Journal of Sciences)
Cataract is a leading cause for avoidable blindness. Age-related cataract is a multifactorial disease, affecting patients over 60 years old. Diabetes mellitus (DM), arterial hypertension (AH) or a combination of both are risk factors for developing a cataract. The aim of the study is to evaluate the prevalence of DM and AH among cataract patients. After an informed consent, cataract patients were randomly chosen to participate in the study. Diagnostic criteria for AH were defined as: systolic blood pressure higher than 140 mmHg, diastolic higher than 90 mmHg and the usage of antihypertensive therapy. Diabetic patients (medical history of DM or reported usage of antidiabetic drugs) were divided in two groups: Type I DM if the patient is on insulin treatment before the age of 30 years, and Type II DM if the patient is on antidiabetic or insulin treatment after the age of 30 years. A total of 126 cataract patients on average age of 66, 2 years participated the study. The youngest patient was a 29 years old female with type I DM and the oldest - 88 years old AH female. There were 63 AH patients (50%) , 2 with type I DM (1.6%), 6 with type II DM (4.8%), 6 patients with AH and type I DM (4.8%), and 11 patients with AH and type II DM (8.7%). 38 patients had no DM or AH (30.2%), among them 20 had no comorbidities. Systemic AH and DM are non-infectious epidemic diseases. According to our study cataract formation in type I DM patients occurs earlier than in diabetes type II DM and hypertensive patients. Type II DM patients develop cataract earlier. We found no significant difference between the average ages of cataract surgery in AH patients and otherwise healthy patients (without comorbidities). Hypertension was found in the majority of cataract patients (50%) and prevalence of diabetes mellitus was 19.9%. We can speculate that many cataract patients in Bulgaria do not undergo surgery due to their socioeconomic status. Hypertension and diabetes mellitus should be better controlled in order to decrease the incidence of visual loss caused by cataract.